Comparison of the gut microbiota and metabolism in different regions of Red Swamp Crayfish (Procambarus clarkii) - Liu, Songyi; Wang, Ziyan; Wang, Ze; Wu, Qiaoli; Zhou, Jun; Wang, Rixin; Han, Jiaojiao; Su, Xiurong (Frontiers in Microbiology, 2023)
The gut microbiota is very important for maintaining the homeostasis and health of crustaceans. Many factors affect the gut microbiota of crustaceans, one of which is temperature. However, it is currently unclear how temperature affects the gut microbiota and metabolites of Procambarus clarkii.: Using metagenomic sequencing and gas chromatography-mass spectrometry (GC-MS) techniques, the gut microbiota and metabolites of P. clarkii from Hubei (HB), Jiangsu (JS), Shandong (SD), and Zhejiang (ZJ) in China were investigated. Results: Under the impact of temperature, the gut microbiota and metabolites of P. clarkii exhibit a specific trend of change. The primary pathogenic bacteria affecting P. clarkii are Citrobacter, Enterobacterium, and Aeromonas, which are affected by temperature. Two metabolites, sugars and amino acids, are regulated by temperature. Implication: This study demonstrated that the gut microbiota and gut metabolites of P. clarkii were considerably affected by temperature. It provides a theoretical basis for the systematic study of P. clarkii and provides a basis for a healthy culture of P. clarkii. key points: 1. Gut microbiota and metabolites of Procambarus clarkii were compared for the first time from four representative habitats. 2. There are effects of temperature on Procambarus clarkii metabolites and gut microbiota.3. Procambarus clarkii from various settings were compared using the combined study of their metabolites and gut microbiota.